Full Multipartite Entanglement of Frequency-Comb Gaussian States - Gerke, S.; Sperling, Jan; Vogel, W.; Cai, Y.; Roslund, J.; Treps, N.; Fabre, C. (Physical Review Letters)

Microwave Experiments Simulating Quantum Search and Directed Transport in Artificial Graphene - Böhm, Julian; Bellec, Matthieu; Mortessagne, Fabrice; Kuhl, Ulrich; Barkhofen, Sonja; Gehler, Stefan; Stöckmann, Hans-Jürgen; Foulger, Iain; Gnutzmann, Sven; Tanner, Gregor (Physical Review Letters)

Photon-Statistics Excitation Spectroscopy of a Quantum-Dot Micropillar Laser - Kazimierczuk, T.; Schmutzler, J.; Aßmann, M.; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M. (Physical Review Letters)
We introduce photon-statistics excitation spectroscopy and exemplarily apply it to a quantum-dot micropillar laser. Both the intensity and the photon number statistics of the emission from the micropillar show a strong dependence on the photon statistics of the light used for excitation of the sample. The results under coherent and pseudothermal excitation reveal that a description of the laser properties in terms of mean input photon numbers is not sufficient. It is demonstrated that the micropillar acts as a superthermal light source when operated close to its threshold. Possible applications for important spectroscopic techniques are discussed.

Uncovering Quantum Correlations with Time-Multiplexed Click Detection - Sperling, Jan; Bohmann, M.; Vogel, W.; Harder, G.; Brecht, Benjamin; Ansari, V.; Silberhorn, Christine (Physical Review Letters)

Structural Quantification of Entanglement - Shahandeh, F.; Sperling, Jan; Vogel, W. (Physical Review Letters)

Pseudorotational Epitaxy of Self-Assembled Octadecyltrichlorosilane Monolayers on Sapphire (0001) - Steinrück, Hans-Georg; Magerl, A.; Deutsch, M.; Ocko, B. M. (Physical Review Letters)

Direct Quantitative Electrical Measurement of Many-Body Interactions in Exciton Complexes in InAs Quantum Dots - Labud, P. A.; Ludwig, A.; Wieck, A. D.; Bester, G.; Reuter, Dirk (Physical Review Letters)

Symmetry-Selective Third-Harmonic Generation from Plasmonic Metacrystals - Chen, Shumei; Li, Guixin; Zeuner, Franziska; Wong, Wing Han; Pun, Edwin Yue Bun; Zentgraf, Thomas; Cheah, Kok Wai; Zhang, Shuang (Physical Review Letters)

Tomography by Noise - Harder, G.; Mogilevtsev, D.; Korolkova, N.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Driven Quantum Walks - Hamilton, Craig S.; Kruse, Regina; Sansoni, Linda; Silberhorn, Christine; Jex, Igor (Physical Review Letters)
Keywords: General Physics and Astronomy